1998
DOI: 10.1046/j.1365-3156.1998.00235.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of chemoprophylaxis and other determinants of malaria in travellers to Kenya

Abstract: Malaria importation from Kenya could be reduced substantially (34%) by eliminating inappropriate medical advice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 10 publications
3
8
0
Order By: Relevance
“…A predominance of imported malaria infections in male patients has been documented before ( 2 , 5 , 18 , 19 ); men are often also less compliant with chemoprophylaxis than women ( 5 ). We also found that children <6 years of age had a significantly higher risk of being reported with malaria.…”
Section: Discussionmentioning
confidence: 84%
“…A predominance of imported malaria infections in male patients has been documented before ( 2 , 5 , 18 , 19 ); men are often also less compliant with chemoprophylaxis than women ( 5 ). We also found that children <6 years of age had a significantly higher risk of being reported with malaria.…”
Section: Discussionmentioning
confidence: 84%
“…The estimates of the prophylactic effectiveness are based on a review of literature on travel medicine malaria studies [19-21]. …”
Section: Methodsmentioning
confidence: 99%
“…Although Hong Kong enjoys a healthcare infrastructure similar to those of other developed nations, at the time of this assessment relatively few organized programmes provided specialized pre-travel services. The availability of effective interventions to reduce travel health risks abroad [14][15][16][17][18][19] and the high frequency of travel among Hong Kong residents underscore the need for travel medicine services in Hong Kong. In this study we assessed the travel health care needs of Chinese residents in Hong Kong by examining travel-related health problems of returning residents and by understanding their use of travel health services before or after travel.…”
Section: Existing Travel Medicine Services In Hong Kongmentioning
confidence: 99%